Incidence of treated alcoholism in north-east Scotland, Orkney, and Shetland fishermen, 1966-70. Issue 1 (February 1982) - Rix, K J; Hunter, D; Olley, P C
Abstract : The psychiatric case register for the north-east of Scotland has been used to calculate the rates for first contact with a diagnosis of alcoholism by fishermen and non-fishermen in the years 1966-70. In each of these years the fishermen had higher rates than non-fishermen as a whole and also higher rates than the non-fishermen from social class IV, which is the social class to which most fishermen belong. The smaller differences between the rates of fishermen and non-fishermen in 1969 and 1970 relative to 1966, 1967, and 1968 may reflect a preferential "shedding" of older alcoholic fishermen at a time when there was a greater than usual contraction in the size of the work force. Differences between the rates for fishermen and non-fishermen were also evident in the age groups 20-29, 30-39, 40-49, and 50-59, being most pronounced in the 20-29 group. The findings are consistent with fishing being an occupation with a high risk for alcoholism.